The Important Role of Literacy in Increasing the Potential of Indonesian Students and Students - Anita Candra Dewi; Rismayanti Rismayanti; Sulistia Waty; Nur Sabrinah; Samsul Samsul; Muh Fatwa Ramadhanul (MultiTech Publisher, 2023)
To support this, the Ministry of Education and Culture developed the Literacy Movement in Schools (GLS). GLS aims to foster a culture of reading, GLS, writing, listening, speaking. (literacy), and selecting information from school members, both principals, students and teachers, which leads to the ability to understand information critically and reflectively. These skills are very necessary in creating creative-productive learning. The theoretical and empirical results of the study show that literacy has a significant role in productive creative learning. These roles include (1) the literacy movement in schools is able to develop critical thinking skills which are very necessary in implementing creative-productive learning, (2) literacy skills are needed in exploratory activities in creative-productive learning, namely by reading, writing, sorting information to solve problems. and discovering new concepts, (3) literacy skills will empower students to conduct exploration, conduct observations, interviews, conduct experiments, and be wise in sorting information from various sources thereby increasing the effectiveness of implementing creative-productive learning in schools.